The Impact of Qur’anic Narratives on Education:" The Story of Joseph (peace be upon him) as a Model" - Fatma ALSeddig Ahmed ELJaadi; Aisha Mohamed Ali Alghwail (Journal of Scientific and Human Dimensions, 2025)
This research aims to examine the Qur’anic stories, which represent a broad and multidimensional educational tool in all education areas, effectively contributing to building of Islamic society and the teaching of moral values. The story of Joseph (peace be upon him) is one of the most important examples of this method of story-based education, as it encompasses events and incidents between father and children, between siblings, and between the self and its instincts. This, in itself, represents a form of self-education. The study explores the situations in which human psychological states, such as anger, envy, fear, loss, wealth, and poverty, appear. It attempts to reconnoitre the styles of the Holy Qur’an that call for maintaining of noble morals. It demonstrates that educators must care for the psychological states and provide those under their care with advice appropriate to their circumstances. This also emphasizes the miraculous nature of the holy Qur’an through its exploration of the inner state of the human soul and knowing of its conditions. It precedes all research and analysis conducted by psychological and educational sciences over many decades. To clarify this, the study has relied on examining the Qur’anic meanings and linking them to the conditions of the souls in this story, then comparing them to the educational methods adopted by pioneers of modern education. The surah thus provides a model for raising individuals within families, instilling in them the ability to confront the negative phenomena that are so prevalent in society.